Contribution of waste segregation to GHG emissions, land usage, and health risk of NMVOC exposure: a study in Malaysia - Rangga, Josfirin Uding; Syed Ismail, Sharifah Norkhadijah; Rasdi, Irniza; Karuppiah, Karmegam (Springer Japan, 2022)
The present study examined greenhouse gas (GHG) emissions, land usage, cost of land use, and health risk exposure to non-methane volatile organic compounds (NMVOC). Waste volume was analysed using the mathematical models obtained from previous literature. The key findings highlighted that the average direct methane (CH4) emissions of landfilled waste were 109 thousand tonnes per year, equivalent to 2.74 million tonnes of carbon dioxide (CO2) per year. Waste segregation has reduced direct CH4 emissions from 112 thousand tonnes in 2014 to 106 thousand tonnes in 2018, in line with the increase in waste diverted from landfills. About 32.08 ha/yr. of the land area were used for waste disposal in landfills that costing USD 1.83 million per year. The waste segregation practice saved approximately 20.10 × 103 ha/yr. of landfill areas, which saves USD 1.15 thousand/yr. Hydrogen sulphide was the main sulphur compound emitted in landfills (103 m3/yr.). There was an acceptable health risk exposure to NMVOC for all groups except exposure to Chlorodifluoromethane and Methyl ethyl ketone (Health Index > 1) for the child group. In the long run, the segregation practice demonstrated a potential reduction in environmental burden with strengthened strategy and empowerment in policy and legislation.